Prevalence of Extracranial venous Narrowing on Magnetic Resonance Venography is Similar in People with Multiple Sclerosis, Their Siblings, and Unrelated Healthy Controls: A Blinded, Case-Control Study. Issue 2 (May 2017) - Martin, Nancy; Traboulsee, Anthony L.; Machan, Lindsay; Klass, Darren; Ellchuk, Tasha; Zhao, Yinshan; Knox, Katherine B.; Kopriva, David; Lala, Shantilal; Nickel, Darren; Otani, Robert; Perera, Warren R.; et al.
Purpose: The study sought to assess and compare the prevalence of narrowing of the major extracranial veins in subjects with multiple sclerosis and controls, and to assess the sensitivity and specificity of magnetic resonance venography (MRV) for describing extracranial venous narrowing as it applies to the chronic cerebrospinal venous insufficiency theory, using catheter venography (CV) as the gold standard. Methods: The jugular and azygos veins were assessed with time-of-flight MRV in this assessor-blinded, case-control study of subjects with multiple sclerosis, their unaffected siblings, and unrelated controls. The veins were evaluated by diameter and area, and compared with CV. Collateral vessels were also analyzed for maximal diameter, as a potential indicator of compensatory flow. Results: A high prevalence of extracranial venous narrowing was demonstrated in all study groups, collectively up to 84% by diameter criteria and 90% by area, with no significant difference between the groups when assessed independently ( P = .34 and .63, respectively). There was high interobserver variability in the reporting of vessel narrowing (kappa = 0.32), and poor vessel per vessel correlation between narrowing on MRV and CV (kappa = 0.064). Collateral neck veins demonstrated no convincing difference in maximum size or correlation with jugular narrowing. Conclusion: There is a high prevalence of narrowing of the major extracranial veins on MRV in all 3 study groups, with no significant difference between them. These findings do not support the chronic cerebrospinal venous insufficiency theory. Although MRV has shown a high sensitivity for identifying venous narrowing, time-of-flight imaging demonstrates poor interobserver agreement and poor specificity when compared with the gold standard CV.